A new genus and species of Elcanidae (Insecta: Orthoptera) from Cretaceous Burmese amber - Heads, Sam W.; Thomas, M. Jared; Wang, Yinan (Zootaxa, 2018)
A new genus and species of Elcanidae (Insecta: Orthoptera) is described from mid-Cretaceous Burmese amber. Elcanonympha diana gen. et sp. nov. is known from a single, complete nymph and is distinguished from other elcanids by the pronotum cut by a single transverse sulcus, the dorsal margin of the metafemoral genicula with a row of prominent apical denticles, and the distal third of the metabasitarsus bearing a row of apically directed scale-like spines on the ventral surface.